Pengaruh karakteristik aset non operasional pada kontribusi pemanfaatan oleh pihak ketiga :: Studi pada pemerintah provinsi DKI Jakarta tahun 2009 - AIZZANI, Yustita Risqi Noor ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Demand of land drives people to lease government’s assets due to space scarcity. Government does not rely land lease payment on consistent basis. This research purpose is to analyze the dependence of land lease payment on independent variables using reggression analysis. As result, independent variables explain statistical relationship the dependence of land lease annual payment on land space, building space, road width, and flooding risk as much as 40.44 percent of it simultaneously. Although, only land space and building explain significant statistical relationship the dependence of land lease annual payment. Both road width and flooding risk explain the relationship insignificantly.